Lead (Pb) isotope ratios from ice core samples from the Puruogangri ice cap and the Dasuopu glacier - M. Roxana Sierra-Hernández; Franco Marcantonio; Lonnie G. Thompson (Scientific Data)
Abstract We provide here the isotopic composition of Pb (204Pb, 206Pb, 207Pb, and 208Pb) in ice cores from two sites, the Puruogangri ice cap in central Tibet and the Dasuopu glacier in the Himalayas. We used non-continuous discrete archived ice core samples that have been previously used for trace element analysis spanning ~36 ka (BP) to 2015. Measurements were performed using a Neptune Plus Multicollector ICPMS with minimal sample preparation. Lead (Pb) isotopes can be used to effectively distinguish between natural and anthropogenic sources, providing insight into specific anthropogenic processes and their geographical origins due to their immunity to fractionation by physical or chemical processes.